Krasoslovje v razvojnih izzivih na krasu = Karstology and Development Challenges on Karst Voda = Water - Knez, Martin; Petrič, Metka; Slabe, Tadej (Carsologica, 2011)
A good knowledge of the natural and cultural heritage of karst is a precondition for the rational planning of life on it. We try to organize the knowledge to make it as useful as possible for planners. We are involved in individual projects related to the regional planning, water supply systems, the construction of transportation infrastructure, the closure of landfills in karst areas, the collection of data on karst caves and their protection, karst ecology and determining the extent of human influence on the karst underground. A new book series Karstology and development challenges on karst was designed to present the results of completed and new projects to a broader public.The first book with the subtitle Water contains selected directly applicable research studies on karst waters, their characteristics, endangerment, and protection. It is composed of ten chapters, which can be grouped into three main themes. In the introduction the importance, characteristics and vulnerability of karst aquifers are presented,then various case studies of pollution and endangerment are described (traffic, landfills, military objects, flooding), and at the end some guidelines for the protection of karst water sources are summarized. The book is a bilingual publication in Slovene and English. It is aimed at a broad circle of users, researchers, students and planners.